Dakwah yang Menggerakkan: Ustaz Abdul Somad dan Komunikasi Islam - Nasution, Naufal Rifqi (Prophetica : Scientific and Research Journal of Islamic Communication and Broadcasting, 2023)
This study aims to analyze the da'wah communication strategies of Ustaz Abdul Somad (UAS) through three approaches: digital mass communication, interpersonal communication, and constructivism within the framework of Islamic communication theory. This research uses a descriptive qualitative method with a case study approach. The findings show that (1) digital media platforms such as YouTube and Instagram are effective in reaching Generation Z through visual language and concise narratives; (2) UAS's interpersonal communication in face-to-face sermons strengthens the reception of da'wah messages through emotional closeness; (3) the constructivist approach allows audiences to actively construct the meaning of da'wah messages. Overall, this study reveals that integrating Islamic communication theory into UAS's da'wah results in communication that is not only informative but also transformative, inspiring behavioral change in religious practice. Keywords : Da'wah, Ustaz Abdul Somad, Islamic Communication, Digital Media, Constructivism